Enactment supports unitisation of action components and enhances the contribution of familiarity to associative recognition - Zhao, Min-Fang; Zimmer, Hubert D.; Zhou, Xiaoyan; Fu, Xiaolan (Journal of cognitive psychology (Hove, England), 2016)
Memory for actions is usually better following subject-performed tasks (SPT) than verbal tasks (VT). We hypothesised that enactment unitises the components of actions such that familiarity can support associative recognition following SPT. To examine this hypothesis, participants studied verb-object pairs in a SPT or VT condition. During testing, they discriminated between intact, recombined and new items and made Remember/Know judgments; additionally, their EEGs were recorded. Associative recognition was better following SPT than VT. Early frontal event-related potentials (ERPs) were graded according to the item status following SPT, but no such effects were found after VT. Similarly, the late parietal ERPs were graded following SPT, whereas these effects were smaller and did not differ between intact and recombined items following VT. We conclude that enactment unitised the action and object so that familiarity could contribute to associative recognition and that recollection became sensitive to the amount of the matching associative information.